2019
DOI: 10.1186/s12944-019-1069-5
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphisms contribute to statin response in Chinese ASCVD patients with dyslipidemia

Abstract: Background Apolipoprotein E (ApoE) plays an important role in lipid metabolism and clearance. Statins are the most common drugs used to modulate the lipid profile in the clinic therapy; the associations between ApoE polymorphisms and statin response to lipids were inconsistent in previous studies among different ethnicities. Our study aimed to demonstrate the relationships among the statins response and the ApoE gene common polymorphisms and lifestyle risk factors in Chinese arteriosclerotic cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…DNA samples were then randomly placed on batches of 96-well plate. Genotyping of APOE was performed according to the manufacturer’s instructions [21]. For the purpose of quality control, 5% of samples were repeated and non-template controls were set in each plate.…”
Section: Methodsmentioning
confidence: 99%
“…DNA samples were then randomly placed on batches of 96-well plate. Genotyping of APOE was performed according to the manufacturer’s instructions [21]. For the purpose of quality control, 5% of samples were repeated and non-template controls were set in each plate.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Although there have been several studies on the role of APOE polymorphism in lipid-lowering therapy using statins, other studies have reached inconsistent conclusions. 14 The relationship between APOE genotypes and statin efficacy remains controversial and inconclusive. In this study, we investigated a possible correlation between APOE polymorphism and the lipid-lowering efficacy of atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…22 Importantly, a comparison of the lipid-lowering effect among genotypes revealed that ε4 carriers exhibited the smallest decrease in the levels of LDL-C and TC, consistent with findings of previous studies where the ε4 allele seemed to have an inadequate response to statin therapy compared to carriers of other alleles. 23 Age, gender and diseases such as diabetes have been reported as factors that influenced the effectiveness of statins. 24 In our study, baseline characteristics such as age, gender and diseases were similarly distributed among APOE genotypes, which may reduce the factors influencing the lipid-lowering efficacy of statins to an extent.…”
Section: Discussionmentioning
confidence: 99%
“…At present, clinical medications ideas for ASCVD mainly focus on correcting of atherogenic dyslipidemia and platelet aggregation. The clinical efficacy of statins and aspirin has been well-established (5,6). Although current atherosclerosis medications can partially relieve the symptoms of ASCVD patients, gastrointestinal reactions, liver and kidney damage, etc.…”
Section: Introductionmentioning
confidence: 99%